Necrophagous flies assemblages: Spatio-temporal patterns in a Neotropical urban environment - Battan Horenstein, Moira (2018)
Species composition, richness, and relative abundance of the communities of Calliphoridae, Muscidae, and Fanniidae in Córdoba city, Argentina was assessed, and how these characteristics are affected by seasonal and anthropogenic conditions was studied. The study was carried out in thirteen sites with various levels of urbanization during 2014 and 2015, comparing two seasons: the warmer-wet summer and the cold-dry winter. Adult flies were collected in each site using two traps baited with hydrated bone meal. A total of 1683 flies were collected, belonging to twelve genera and 22 species. Several of the species collected are relevant to forensic sciences. The most frequent species were Hydrotaea aenescens (Muscidae) and Fannia fusconotata (Fanniidae). No differences in necrophagous fly richness or relative abundances between the central urban sites and the periphery suburban sites were observed; however, richness was significantly correlated with local (250 m buffer area) built-up density. Species composition differed between the urban and suburban sites. Seasonal differences were also detected: the relative abundances per species were more even in the summer. Dissimilarities in the assemblages were mainly due to differences in the relative abundances of some species, reflecting their adaptability to landscapes with different degree of urbanization. Regardless of season or urbanization density, species richness and effective number of species were higher in traps placed in the sun as opposed to shade. Taken together, these results suggest that in Córdoba city both landscape and local factors explain variations in the necrophagous fly community.